2001
DOI: 10.2134/agronj2001.933570x
|View full text |Cite
|
Sign up to set email alerts
|

Tillage and Pest Management Considerations in a Peanut–Cotton Rotation in the Southeastern Coastal Plain

Abstract: Radical changes in crop production have occurred in the southeastern USA in recent years. Peanut (Arachis hypogaea L.) and cotton (Gossypium hirsutum L.) are now planted in direct rotation, and conservation tillage is commonly used for both crops. Comprehensive data is lacking on crop and pest management recommendations in those systems, so a long‐term study was conducted in Tifton, GA on the effects of tillage systems on crop and pest management in a peanut–cotton rotation. Systems evaluated were conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
68
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 9 publications
7
68
0
Order By: Relevance
“…A peanut-cotton rotation is popular among growers in the Southeast (Johnson et al, 2001). Current cotton recommendations indicate that the residue of a high-yielding soybean or peanut crop may contribute up to 34 kg N ha −1 to the subsequent cotton crop (Adams et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A peanut-cotton rotation is popular among growers in the Southeast (Johnson et al, 2001). Current cotton recommendations indicate that the residue of a high-yielding soybean or peanut crop may contribute up to 34 kg N ha −1 to the subsequent cotton crop (Adams et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Contrasts between tillage treatments revealed that only during one season (2004), were differences shown between the conservation tillage systems (both WST and NST) and the conventional tillage system. Narrow-strip tillage or wide-strip tillage were individually superior to conventional tillage in three seasons out of five, however not always in the Conventional 3650 4270 3740 2900 3430 Wide-strip 3020 3880 4410 3230 4000 Narrow-strip 3750 4230 4290 3490 (Chapin et al, 2001;Johnson et al, 2001;Wiatrak et al, 2004).…”
Section: Resultsmentioning
confidence: 92%
“…Seven studies, four of which were conducted with the virginia market type, favored conventional, high intensity tillage practices that could not be considered conservation tillage Grichar and Boswell, 1987;Jordan et al, 2001;Jordan et al, 2003;Minton et al, 1991;Wright and Porter, 1991a;Wright and Porter, 1995). Not surprisingly, seven other studies showed no differences in conservation tillage systems versus conventional tillage (Chapin et al, 2001;Grichar, 2006;Grichar and Smith, 1992;Grichar and Smith, 1992;Johnson et al, 2001;Wiatrak et al, 2004). In fact, a comparison of the sources named above indeed shows the same authors with studies that support conservation tillage, give it no clear advantage, or even oppose conservation tillage for peanut.…”
mentioning
confidence: 95%
“…Johnson et al (2001) tested peanut yield response to conventional, reduced, and minimum tillage in a peanut-cotton rotation in Georgia and found that over 5 yr there were no differences in peanut yield among tillage systems. Tubbs and Gallaher (2005) compared peanut yield of five tillage treatments in Florida and suggested that strip tillage systems, with proper management provide an advantage in yield over conventional tillage systems.…”
Section: Resultsmentioning
confidence: 99%
“…Studies suggest that there are considerable differences among different tillage methods in input costs, soil impact or crop yields (Johnson et al, 2001;Sidhu and Duiker, 2006). Tillage methods influence not only soil properties SiriPrieto et al, 2007a), but also crop yields Reeves and Mullins, 1995;Siri-Prieto et al, 2007b).…”
mentioning
confidence: 99%